Novel optical cryptography using PANDA ring resonator for highly secured communication - Putthacharoen, Rattipong; Juleang, Pakorn; Mitatha, Somsak; Yupapin, Preecha P. (My University, 2011)
We propose a novel method of an optical cryptography using the dark-bright soliton conversion control in a modified adddrop optical filter. By using the control arrangement, the obtained outputs of the dynamic states of dark-bright soliton can be used to form the key suppression for communication security application, in which the key recovery can be obtained by controlling the adddrop filter outputs. The optical cryptography consists of an adddrop filter which is used to generate the encryption and decryption keys from the optical keys (LIP signals). A Mach-Zehnder interferometer is used for multiplexing and de-multiplexing operations. Simulation results obtained shows, that the proposed system can be used to form a high security communication system. © 2011 Society of Photo-Optical Instrumentation Engineers (SPIE).
Keywords: Communication security; Key recovery; Key suppression; Optical cryptography